Infectivity versus Seeding in Neurodegenerative Diseases Sharing a Prion-Like Mechanism - Natalia Fernández-Borges; Hasier Eraña; Saioa R. Elezgarai; Chafik Harrathi; Mayela Gayosso; Joaquín Castilla (International Journal of Cell Biology)
Prions are considered the best example to prove that the biological information can be transferred protein to protein through a conformational change. The term “prion-like” is used to describe molecular mechanisms that share similarities with the mammalian prion protein self-perpetuating aggregation and spreading characteristics. Since prions are presumably composed only of protein and are infectious, the more similar the mechanisms that occur in the different neurodegenerative diseases, the more these processes will resemble an infection. In vitro and in vivo experiments carried out during the last decade in different neurodegenerative disorders such as Alzheimer's disease (AD), Parkinson's diseases (PD), and amyotrophic lateral sclerosis (ALS) have shown a convergence toward a unique mechanism of misfolded protein propagation. In spite of the term “infection” that could be used to explain the mechanism governing the diversity of the pathological processes, other concepts as “seeding” or “de novo induction” are being used to describe the in vivo propagation and transmissibility of misfolded proteins. The current studies are demanding an extended definition of “disease-causing agents” to include those already accepted as well as other misfolded proteins. In this new scenario, “seeding” would be a type of mechanism by which an infectious agent can be transmitted but should not be used to define a whole “infection” process.